Oral candidosis by Candida albicans in normal and xerostomic mice - Totti,Marilda Aparecida Gonçalves (2004)
The aim of this study was to analyze the effect of sialoadenectomy on the development of oral candidosis after one or four inoculations of Candida albicans. Initially, a suspension containing 10(8) cells/ml of C. albicans ATCC 36801 was prepared. Seventy-eight sialoadenectomized mice and a similar amount of mice with normal salivary flow received a single inoculation of C. albicans suspension. Another group with a similar number of mice received 4 inoculations. The control group consisted of 6 sialoadenectomized mice and 6 mice with normal salivary flow that were not inoculated with C. albicans. Candidosis development was studied histologically in the tongue of the animals 1, 2, 3, 5, and 8 days after inoculation and at 15-day intervals up to 165 days. According to the results obtained, it could be concluded that sialoadenectomy and a higher frequency of yeast inoculation influenced the presence and extension of candidosis lesions.